If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 9 = 12x + 12 Reorder the terms: 9 + 9x = 12x + 12 Reorder the terms: 9 + 9x = 12 + 12x Solving 9 + 9x = 12 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 9 + 9x + -12x = 12 + 12x + -12x Combine like terms: 9x + -12x = -3x 9 + -3x = 12 + 12x + -12x Combine like terms: 12x + -12x = 0 9 + -3x = 12 + 0 9 + -3x = 12 Add '-9' to each side of the equation. 9 + -9 + -3x = 12 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = 12 + -9 -3x = 12 + -9 Combine like terms: 12 + -9 = 3 -3x = 3 Divide each side by '-3'. x = -1 Simplifying x = -1
| 58n=172 | | 40000a+200b=6 | | a-18=22 | | 172=58n | | 3xover+8=5 | | 2.3x^2-1.9x=6.8 | | -4x+-12=2x+24 | | -2(4g)= | | 10000a+100b+4.7=8.7 | | 3/x-2/y | | .25x^2+x=-1 | | 13x-4=12x-6 | | 5x+1=2.2 | | 112-15=b | | 13x-7=5x-47 | | 12x+10=5x+24 | | 3x-12=9x-72 | | 9x+4=5.8 | | S/6-12=-16 | | 2+r=5 | | 3.3x+5.7y-6.7=0 | | 4x-11=10x-11 | | 4.25x+3=-3x^2 | | 3x+5=10x-30 | | (3.5x)+x=100 | | √8/21 | | 13x-9=8x-34A-5B-4C-2D-7E-1 | | 7x-11=8x-14 | | X-18y=45 | | F(xy)=2x^2+3xy+4y^2-5x+2y | | 4x+7=12x-33 | | 5x+12=4x+12 |